EXPLORING STUDENTS' PROBLEM-SOLVING SKILLS ON DIRECT CURRENT ELECTRICAL IN VOCATIONAL HIGH SCHOOL - Luh Sukariasih; Erniwati Erniwati; La Tahang; Andi Marwanti Panre (EDUSAINS, 2024)
This research aimed to explore the problem-solving skills of Vocational High School in Kendari students in direct current electricity. The research used the descriptive-quantitative method, and the research sample was twelve science-grade students in Vocational High School in Kendari. The research instruments already used as several questions and problem-solving skills had 0,88 validity. Data collections were tests and interviews. The result has obtained problem-solving skills with low criteria. Research results show the indicator of useful description in higher criteria, a physics approach and a specific application of physics in low criteria. Otherwise, mathematical procedures and logical progression were included in very low criteria. Students have good abilities in useful descriptive indicators. Another indicator is that students are experiencing difficulties. Students need help untangling electrical circuits in series or parallel and applying Kirchhoff's I and II laws. The problem of applying mathematical procedures was algebra and fractions in electrical circuits. This research can be used to improve students' problem-solving skill on direct current electrical material for Vocational high school physics subjects.